Nd:YAG Laser in the Treatment of Nail Psoriasis: Clinical and Dermoscopic Assessment - Yasmin Hesham Ali Elwan; Amira Azim; Michela Starace; Hala Shawky Abd Elhafiz (Mattioli1885, 2021)
Background: The Nd:YAG laser has emerged as a promising modality for the management of nail psoriasis owing to its ability for deep penetration of the skin surface, which has the advantage of destroying deep vessels. Objective: To assess the efficacy and safety of Nd:YAG laser in treating nail psoriasis. Methods: The present study was a randomized controlled study, conducted on 20 patients of both sexes (age older than 12 years) with mild to moderate psoriasis with nail involvement. We utilized facial telangiectasia parameters of Nd:YAG laser and beam diameter of 2.5 mm. Laser energy started with 110 J/cm2 in the first session and 130 J/cm2 in the rest of the sessions. Sessions were performed once monthly for up to 6 sessions. Results: We found no statistically significant difference in total Nail Psoriasis Severity Index (NAPSI) and nail bed scores before and after treatment among the treated group. However, there was statistically significant improvement in nail matrix score after treatment. On the other hand, the control group did not show any statistically significant changes for all scores throughout the study, except for the nail matrix score mean difference (0.35 ± 1.23 vs -1.00 ± 1.86 in the treated group). The degree of dermoscopic improvement was evident in the treated group (45% vs 25% in the control group). However, it was not statistically significant because of small sample size. The patients' satisfaction and the external investigator's assessment showed statistically significant negative correlation with total NAPSI mean difference in the treated group. Conclusion: The role of Nd:YAG laser in nail psoriasis is still controversial.